Human Rights and The New Normal Challenges: A Sharia Perspective - Muchtar, Ayi Ishak Sholih (TAJDID, 2022)
This study aims to elaborate ideas and debates on human rights in the era of the Covid-19 pandemic. The point of view of this study is Islamic Sharia. This study uses a literature review method complemented by personal reflection to connect Islamic sharia ideas with social dynamics during the pandemic. Several relevant pieces of literature are reviewed and analyzed to find the suitable core of sharia ideas. By exploring some basic principles of human rights, this study concludes that in this era of the Covid-19 pandemic, some people view government policies as contrary to human rights because they have to experience many restrictions and pressures, such as the obligation to wear masks, vaccinations, social distancing, restrictions on worship activities, isolation. They also feel that their human rights have been violated by regulations requiring them to wear masks, feeling insecure by the threat of contracting the virus, losing their jobs, threats of death, and so on. On the other hand, some other humans support regulations and legal rules based on health protocols. The support of this second group is also for the sake of protecting human rights. They support the government’s policy of enforcing health protocols solely to avoid the danger of contagion of Covid-19 which can lead to severity and even death. In the perspective of Islamic Sharia, human rights which are based on freedom are actually limited by the rights of others. Freedom as one of the core of human rights is also balanced with obligations and responsibilities.